2021
DOI: 10.3390/cancers13164012
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation after Lung Cancer Surgery: Prediction, Prevention and Anticoagulation Management

Abstract: Atrial fibrillation (AF) is a common complication of the early postoperative period of various types of surgery, including that for lung cancer. Although induced by the homeostatic alterations related to surgery, there is evidence that it is not a mere stand-alone transitory event, but it represents a relevant complication of surgery, bearing considerable prognostic consequences. Different methods have therefore been explored to predict the occurrence of postoperative atrial fibrillation (POAF) and prevent it.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 93 publications
1
6
0
1
Order By: Relevance
“…There are many reasons related to postoperative atrial fibrillation, and the extent and type of thoracic surgery were reported to affect the likelihood of developing atrial fibrillation. According to these studies, pneumonectomies and lobectomies generally carry a greater risk than wedge resection (>15% vs. 5-15%) [23][24]. In our study, 2 patients (9.52%) in group EL developed atrial fibrillation, and there was no difference in the incidence between group EL and group ES.…”
Section: Accepted Manuscript Fistulasupporting
confidence: 41%
“…There are many reasons related to postoperative atrial fibrillation, and the extent and type of thoracic surgery were reported to affect the likelihood of developing atrial fibrillation. According to these studies, pneumonectomies and lobectomies generally carry a greater risk than wedge resection (>15% vs. 5-15%) [23][24]. In our study, 2 patients (9.52%) in group EL developed atrial fibrillation, and there was no difference in the incidence between group EL and group ES.…”
Section: Accepted Manuscript Fistulasupporting
confidence: 41%
“…Atrial fibrillation is a common early postoperative complication following lung cancer surgery, with an incidence rate of approximately 10% to 20% [20]. This incidence varies depending on the extent of lung resection: rates are lower for wedge resection (2%-4%), intermediate for lobectomy (10%-15%), and higher for pneumonectomy (over 20%) [21]. Known risk factors for postoperative atrial fibrillation include heart failure, hypertension, a history of myocardial infarction, and male gender [22].…”
Section: Discussionmentioning
confidence: 99%
“…showed that the incidence of POAF in patients undergoing thoracic surgery for lung cancer was 19%. Moreover, the incidence varies according to the extent of lung resection, being lower for wedge resections (2–4%), intermediate for lobectomies (10–15%), high for pneumonectomies (>20%) ( 25 ). And to a large extent, POAF has been deemed as a benign and temporary complication of lung cancer surgery, with possible mechanisms such as inflammation, oxidative stress, and autonomic nervous system dysfunction ( 25 ).…”
Section: Discussionmentioning
confidence: 99%